DIRECTIONS FOR ACTIVATING THE DEVELOPMENT OF SMALL AND MEDIUM BUSINESSES IN WAR CONDITIONS - TULCHYNSKA, Svitlana; SHYLO, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The purpose of the article is to substantiate the directions for activating the activities of small and medium businesses (SMBs) in war conditions on the territory of Ukraine. It is established that in relation to the pre-war problems of SMBs development, including insufficient access to financial resources, high risks of doing business, uncertainty of the market environment, etc., the war created new challenges for business, which is due to the destruction of infrastructure, logistical problems, a decrease in the purchasing power of the population, personnel challenges due to migration and mobilization of the population. Otherwise, the threat of physical destruction and damage to fixed assets of SMBs is preserved. The above requires the development of measures to support SMBs. The directions for activating the activities of SMBs in war conditions are identified, which include: diversification of production, search for new sales channels; optimization of costs; support for state financing; innovative development strategies. Diversification of products and services provides an expansion of the range of goods/services that meets new consumer needs during the war, which allows you to reduce dependence on one market segment, adapt to changed consumer requirements, increase resilience to market fluctuations, attract new customers. Search for new sales channels through the development of online sales, changing product distribution channels (for example, through digital platforms), favorable reduction of physical restrictions on access to markets and customers, increasing coverage, increasing sales volumes, preserving business in crisis conditions. Cost optimization through the implementation of cost-cutting measures, such as automation, outsourcing, optimization of production processes, which helps reduce production and business management costs, increase resource efficiency, maintain financial stability, improve profitability. Innovative development strategies through the implementation of the latest technologies, in particular digital solutions, automation and innovations in business processes, which contribute to increased productivity, increased innovation and competitiveness. Development of human resources through improving the skills of employees, flexibility in management personnel, adaptation to new conditions, which will make it possible to retain highly qualified employees and effectively adapt to changes.